BELIEF SYSTEM, SISTEM PENGENDALIAN DIAGNOSTIK, SISTEM PENGENDALIAN INTERAKTIF, INOVASI, KINERJA ORGANISASI (STUDI PADA PERUSAHAAN MANUFAKTUR DI JAWA BARAT) - Mariyam Chairunisa (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study aims to examine impact of Management Control System on organizational performance mediated by innovativeness. Contingency and Levers of Control theories are used in this research with data collection and judgment sampling method on manufacturing companies. The data are represented by managers and assistant managers as respondents in West Java Area. The data is collected by post, electronic mail and direct survey from January 27, 2016 to March 2016. Result of this study indicates that management control system consisting belief system and interactive control system have a positive effect and significant on innovativeness and innovativeness ultimately have a positive and significant impact to organizational performance. However, diagnostic control system does not have significant influence to innovativeness. This study solely relies on construct of innovativeness capability.